Pengembangan Relationship Capital Pelaku UKM Agro Di kabupaten Donggala - Djayani Nurdin; Muh. Yunus Kasim; Mohammad Ega Nugraha; Asngadi Asngadi; Husnah Husnah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
One challenge in developing SMEs is still weak access to financial institutions and markets, making it difficult for SMEs to develop. The difficulty of access to financial resources will have an impact on limited business expansion which will result in a weak capacity to expand business volume. On the other hand, weak market access also has an impact on the small market controlled by SMEs which has an impact on small product demand growth. The weakness factor that sticks to SMEs is mainly access to business development. This service program aims to strengthen understanding of the importance of relationship capital for the development of agro-businesses in Tamarenja Village, Donggala Regency. In this community service activity, lecture, question and answer, and discussion methods are used. This training activity is focused on Agro business management training through strengthening business networks. There are three stages in the implementation method, namely the preparation stage, the implementation stage and the evaluation stage. The result of this activity is that agro-business actors in Tamarenja Village can be developed on a wider scale considering the current large market such as opening access for IKN (National Capital City), the growth of the Morowali industrial area, strengthening the Togean tourism industry and growing demand in the local market.